Analisis kritis hubungan quarter life crisis dan toxic relationship pada mahasiswa Jabodetabek di Malang - Pandita, Gavrila (Maliki Interdisciplinary Journal, 2025)
This review article critically analyzes the relationship between Quarter-life crisis and toxic relationship s among university students, focusing on the study entitled “Quarter life crisis and toxic relationship on students: A case study of Jabodetabek Raya in Malang.” The analysis reveals that identity crises during emerging adulthood may undermine emotional stability and increase vulnerability to harmful interpersonal relationships. Gender dimension plays a crucial role, with female students being more prone to experiencing toxic relationship s. Furthermore, the local context of migrant students significantly affects this phenomenon, particularly in terms of social adaptation and emotional support needs. Methodologically, the qualitative case study design allows in-depth exploration but limits generalization. Therefore, future research should integrate quantitative approaches to strengthen empirical evidence and propose practical interventions in higher education settings.